Study of Fodder Plants of Rupandehi - Singh, Anant Gopal (Himalayan Biodiversity, 2017)
Fodder, a type of animal feed, is any agricultural food stuff used specifically to feed domesticated livestock. In the present study 37 plant species belonging to 22 families and 26 genera as fodder plants were recorded form different parts of Rupandehi and its surrounding area.